469 Palliative Care Effect on Survival in Glioblastoma: Who Receives Palliative Care?. (April 2023) - Pando, Alejandro; Patel, Aman; Shaari, Ariana; Choudhry, Hannaan; Eloy, Jean Anderson; Goldstein, Ira M.; Liu, James K.
Abstract : INTRODUCTION: High grade glioma has a poor overall survival with profoundly negative effects on the patient's quality of life and their caregivers. METHODS: The National Cancer Database was analyzed for patterns of care in patients ≥18-years-old who were diagnosed with histologically confirmed grade IV GBM between 2004 and 2017. All statistical analyses were conducted based on univariate and multivariate regression models. RESULTS: A total of 85, 380 patients with the diagnosis of GBM were identified. Of the study population, 2, 803(3.28%) patients received palliative therapy. On multivariate logistic regression analysis, age ≥70 Years (odds ratio[OR] = 1.28, 95% Confidence Interval [CI] = 1.04-1.58; p < 0.001), Medicare (OR = 1.348, CI = 1.13-1.61; p = 0.001), tumor size ≥5 cm (OR = 1.15, CI = 1.01-1.31; p = 0.036), tumor multifocality (OR = 1.69, CI = 1.47-1.96; p < 0.001), lobe overlapping tumor (OR = 2.09, CI = 1.13-3.86; p = 0.018), Charlson-Deyo score >0, receiving treatment at a non-academic/research program, and medium volume of cancers managed at the treatment facility (OR = 1.19, CI = 1.02-1.38; p = 0.026) were independent risk factors associated with an increased chance of receiving palliative care. In contrast, a household income of ≥$40, 227 and high volume of cancer managed at the treatment facility (OR = 0.75, CI = 0.58-0.96; p = 0.02) were independent risk factors associated with decreased palliative care. Patients who received no palliative care had a 2-year overall survival rate longer than those who received palliative care (22% vs. 8.8%; p < 0.001). In patients receiving palliative care, those who received recommended treatment had a 2-year overall survival rate longer than those who declined part or whole recommended treatment (9.1% vs. 3.8%; p = 0.009). CONCLUSIONS: In patients with high grade glioma, receiving palliative care is associated with decreased survival. When receiving palliative care, recommended treatment improves survival almost three-fold compared to those declining part or whole treatment.